High Performance Space Lubrication of MoS2 with Tantalum. (2nd February 2022) - Serles, Peter; Nicholson, Eric; Tam, Jason; Barri, Nima; Chemin, Jean‐Baptiste; Wang, Guorui; Michel, Yann; Singh, Chandra Veer; Choquet, Patrick; Saulot, Aurélien; Filleter, Tobin; Colas, Guillaume
Abstract: Molybdenum disulfide coatings have been employed as lubricants for spacecraft since the 1950s but continue to face major engineering challenges including performance in both terrestrial air and deep space vacuum environments and service lifetimes on the order of decades without maintenance. Co‐deposition of MoS2 with additive compounds provide enhancements in some circumstances but a lubricant which can perform in all space‐facing environments with long lifetimes remains an ongoing problem. Herein, it is demonstrated the multi‐environment adaptable performance of a novel MoS2 + tantalum lubricant coating, which excels as a lubricant in both terrestrial and space environments while the benchmark space‐qualified commercial MoS2 lubricants do not. It is noted that the 10% tantalum additive exhibits preferential oxidation in air to preserve the lubricating ability of MoS2 while forming phases of TaS2, which aid in the exceptional lubrication of MoS2 in ultra‐high vacuum. Additionally, completely different tribofilms of small particles and compact sheets are noted for air and vacuum environments, respectively, which allows for adaptable lubricating mechanisms from a single coating depending on the environment. This novel coating sets the benchmark as the first demonstrated instance of a fully versatile space lubricant which offers high‐performance in both terrestrial and deep space environments. Abstract : A novel MoS2 coating co‐deposited with tantalum shows adaptable lubricating mechanisms that enable it to excel in both terrestrial and deep‐space environments. Addition of tantalum within the MoS2 structure shows equal stability in intercalated or substituted states of Ta in the MoS2, which favors "adaptative" tribochemical response and tribofilm formation.